PPG-based Vital Signs Measurement Using SmartPhone Camera: Review - Ghada Khairi Khessro; AbdulSattar Muhammed Khidhir (NTU Journal of Engineering and Technology)
Due to their growing popularity and rapid performance improvements, smartphones have the potential to be an accurate, low-cost physiological monitoring tool that is useful outside of the clinical setting. Since the cardiac pulse is responsible for the slight color changes in skin, a pulsatile signal that is also known as a photoplethysmographic (PPG) signal can be evaluated by utilizing a digital camera to record a video of your Region Of Interest (ROI).